2014
DOI: 10.1007/s11325-014-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Apps in sleep medicine

Abstract: The tested apps are not accurate enough to replace the common diagnostic standard in therapy. However, they can be a helpful addition. Especially, singles could use them who do not know if their snoring has improved with an OA and do not have anybody to ask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…This study also highlighted that few apps drew from empirical evidence, supporting past research that many sleep apps are based on a limited evidence base. 13,18 Furthermore, from our evaluation of the sleep app descriptions and screenshots provided by the developers, all of the apps except one (the most downloaded and highest rated app) failed to mention the 2-process model of sleep. This model is important as it describes the interaction between circadian processes, which run on a 24-hour rhythm controlled by the central pacemaker in the suprachiasmatic nucleus, and homeostatic processes, which relate to the accumulation of hypnogenic substances within the central nervous system that form during wake hours and dissipate during sleep period, 22 and is vital to understand sleep-wake cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also highlighted that few apps drew from empirical evidence, supporting past research that many sleep apps are based on a limited evidence base. 13,18 Furthermore, from our evaluation of the sleep app descriptions and screenshots provided by the developers, all of the apps except one (the most downloaded and highest rated app) failed to mention the 2-process model of sleep. This model is important as it describes the interaction between circadian processes, which run on a 24-hour rhythm controlled by the central pacemaker in the suprachiasmatic nucleus, and homeostatic processes, which relate to the accumulation of hypnogenic substances within the central nervous system that form during wake hours and dissipate during sleep period, 22 and is vital to understand sleep-wake cycles.…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, other studies examining apps related to a single symptom of sleep (apps only monitoring snoring) found that the apps tested were not accurate enough to replace common diagnostic measures. 18 Finally, while research examining an app to assess sleep by detecting sleep and wake states, daily sleep quality, and global sleep quality demonstrated high accuracy percentages among the sleep states, the data were not compared to objective sleep measures. 19 This study explored the different kinds of information, functions, and evidence features sleep apps contained and what percentage of sleep apps contained these features.…”
Section: Rate My Sleep: Examining the Information Function And Basimentioning
confidence: 99%
“…In this category, a total of 6 articles could be identified [49][50][51][52][53][54]. A pilot study could show the effective measurement of snoring and other symptoms of obstructive sleep apnea by means of an app used during the sleep-medical examination.…”
Section: Studies On Apps Regarding Sleep Medicinementioning
confidence: 99%
“…The app users achieved a weight loss; however, it had no impact on the OSAS [50]. The four review articles on apps regarding "sleep and snoring" [49,[52][53][54] criticized the intransparent management of the assessed data in addition to the fact that often no scientifically confirmed evidence was mentioned or found referring to the analyses and statements of the apps.…”
Section: Studies On Apps Regarding Sleep Medicinementioning
confidence: 99%
“…43 Several authors have evaluated the usefulness of apps for detecting sleep-related parameters. Stippig et al 44 compared some apps for monitoring and recording sleep sounds, concluding that the tested apps were not sufficiently accurate to replace the standard diagnostic methods. Ong et al 45 also reviewed several features provided by sleep analysis apps to record sounds during sleep, and concluded that physicians have to be aware of the most common apps' features and limitations to counsel patients properly when they inquire about them.…”
Section: Audio Recording: Snoring and Breathmentioning
confidence: 99%